Building a Library of Simulated Atom Probe Data for Different Crystal Structures and Tip Orientations Using TAPSim. (18th February 2019) - Kühbach, Markus; Breen, Andrew; Herbig, Michael; Gault, Baptiste
Abstract: The process of building an open source library of simulated field desorption maps for differently oriented synthetic tips of the face-centered cubic, body-centered cubic, and hexagonal-close-packed crystal structures using the open source software TAPSim is reported. Specifically, the field evaporation of a total set of 4 × 101 single-crystalline tips was simulated. Their lattices were oriented randomly to sample economically the fundamental zone of crystal orientations. Such data are intended to facilitate the interpretation of low-density zone lines and poles that are observed on detector hit maps during Atom Probe Tomography (APT) experiments. The datasets and corresponding tools have been made publicly available to the APT community in an effort to provide better access to simulated atom probe datasets. In addition, a computational performance analysis was conducted, from which recommendations are made as to which key tasks should be optimized in the future to improve the parallel efficiency of TAPSim.